Effect of Ultrasonic Pretreatment on Biomethane Potential of Two-Phase Olive Mill Solid Waste: Kinetic Approach and Process Performance - B. Rincón; L. Bujalance; F. G. Fermoso; A. Martín; R. Borja (The Scientific World Journal)
The effect of ultrasound (US) pretreatment on two-phase olive mil solid waste (OMSW) composition and subsequent anaerobic biodegradation was evaluated by chemical oxygen demand solubilization and biochemical methane potential (BMP) tests. OMSW was ultrasonically pretreated at a power of 200 W and frequency of 24 kHz for time periods of 20, 40, 60, 90, 120, and 180 minutes, corresponding to specific energies of 11367, 21121, 34072, 51284, 68557, and 106003 kJ/kg total solids, respectively. In order to evaluate the US pretreatment, a low, medium, and high exposure time, that is, 20, 90, and 180 min, were selected for BMP tests. Methane yields of 311±15, 393±14, and 370±20 mL CH4/g VSadded (VS: volatile solids) were obtained for 20, 90, and 180 minutes, respectively, while the untreated OMSW gave 373±4 mL CH4/g VSadded. From a kinetic point of view, the BMP tests showed a first exponential stage and a second sigmoidal stage. In the first stage, the kinetic constant obtained for US pretreated OMSW at 20 minutes was 46% higher than those achieved for the pretreated OMSW at 90 and 180 minutes and 48% higher than that for untreated OMSW. The maximum methane production rate achieved was 12% higher than that obtained for untreated OMSW.